Bankruptcy Risk in Modern Business : Theoretical, Legal, and Practical Perspectives - Volobuieva, Anna; Halík, Jaroslav, 1961-; Štěrbová, Ludmila, 1957-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This work highlights the theoretical basis of the concept of bankruptcy, and methods for measuring the risk of bankruptcy in advance. This work also highlights the procedure of financial analysis in the perspective of early detection of bankruptcy. The practical part of the work is focused on the assessment of bankruptcy risk in the company Amcor plc, using qualitative and quantitative methods for detecting bankruptcy risk.
Vedoucí práce: Jaroslav Halík
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses